Determinants Of The Timeliness Of Financial Reporting Of Banking Companies Listed On The BEI - Hesty T Salle; Muslimah S Munir; Otniel Safkaur (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The purpose of this study was to analyse the effect of profitability, liquidity, , , leverageaudit and opinioncompany size on the timeliness of financial financial reporting in banking companies listed on the IDX in 2020 - 2022. The tested factors in this study are profitability measured using return on assets (ROA), liquidity measured using current ratio (CR), ), leverage measured using debt to equity ratio (DERaudit opinion measured using dummy , and variablescompany size measured using size (LN). This type of research is quantitative. The sample in this study were 45 banking companies listed on the IDX in 2020 - 2022. technique The sampling in this study was purposive sampling. tool the analytical used is multiple linear regression analysis. The results of the analysis can be concluded that: profitability affects the timeliness of financial reporting. Liquidity affects the timeliness of financial reporting, leverage has no effect on the timeliness of financial reporting. Audit opinion affects the timeliness of financial reporting. Company size affects the timeliness of financial reporting.